If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-4 + 3x) = 8 x + (-4 * -1 + 3x * -1) = 8 x + (4 + -3x) = 8 Reorder the terms: 4 + x + -3x = 8 Combine like terms: x + -3x = -2x 4 + -2x = 8 Solving 4 + -2x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = 8 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = 8 + -4 -2x = 8 + -4 Combine like terms: 8 + -4 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 2x-301=707 | | 9x+3/2=x | | -8x-3(x+4)=x+7 | | -47=7+6x | | 6x=4(x+1)+2x-6 | | a+b=-2 | | 9=-4(2-7x)-5x | | 3/4(8x-12)=0 | | -4(2-7x)-5x=9 | | -6(x+3)+4x+7=5x+8 | | -1(x-27)+3(x+3)=9(x-3) | | 3.4x-1.32=2.04-2.2x | | 9x+9=30 | | 4x+7=30/x | | 14m+9-6m=8m+9 | | (1/6)(8x-7)=(x+7)/12 | | x+3+8x=2x-1 | | 5y+3(y-6)=3(y+2)-2 | | 3x+7=8x-13 | | (1/6)(8x-7)=(x+7/12) | | 2a-5b=38 | | -1(x-12)+2(x+3)=6(x+3) | | 6[9-(-3x-3)]=54x+108 | | P=c+3b+4aforc | | 7(4x-5)-3=28x-38 | | 8z-19=-15+7z | | 9x+8-7(x+1)=6x+4 | | -1(x-12)+2(x+3)=x+3 | | 4x=34+3x-5+7x | | 9x+1=9(x+9) | | 4x+9-67(x+1)=6x+7 | | x^3+3x^2-81x-85=0 |